The unorthodox evolution of major merger remnants into star-forming spiral galaxies - Sparre, Martin; Springel, Volker (Arxiv, 2017)
Galaxy mergers are believed to play a key role in transforming star-forming disk galaxies into quenched ellipticals. Most of our theoretical knowledge about such morphological transformations does, however, rely on idealised simulations where processes such as cooling of hot halo gas into the disk and gas accretion in the post-merger phase are not treated in a self-consistent cosmological fashion. In this paper we study the morphological evolution of the stellar components of four major mergers occurring at z=0.5 in cosmological hydrodynamical zoom-simulations. In all simulations the merger reduces the disk mass-fraction, but all galaxies simulated at our highest resolution regrow a significant disk by z=0 (with a disk fraction larger than 24%). For runs with our default physics model, which includes galactic winds from star formation and black hole feedback, none of the merger remnants are quenched, but in a set of simulations with stronger black hole feedback we find that major mergers can indeed quench galaxies. We conclude that major merger remnants commonly evolve into star-forming disk galaxies, unless sufficiently strong AGN feedback assists in the quenching of the remnant.